DNA topology affects transcriptional regulation of the pertussis toxin gene of Bordetella pertussis in Escherichia coli and in vitro. - Scarlato, V (1993)
The bvg locus of Bordetella pertussis encodes an environmentally inducible operon essential for the expression of virulence genes. We show that in Escherichia coli, the PTOX promoter cloned in cis of the bvg locus is activated and environmentally regulated. Cotransformation of E. coli with the bvg locus cloned in a low-copy-number plasmid and with the PTOX promoter cloned in a high-copy-number plasmid can give rise to two different results. If the PTOX promoter is cloned in the pGem-3 vector, transcription is absent. If the PTOX promoter is cloned in the plasmid pKK232, containing the PTOX promoter between two ribosomal gene terminators of transcription, transcription occurs, although regulation of transcription is abolished. Under these conditions, the intracellular amount of RNA transcripts is increased by adding to the culture medium novobiocin, an inhibitor of bacterial gyrases. In vitro, the transcription of the PTOX promoter is activated on E. coli RNA polymerase supplemented with cell extracts from wild-type B. pertussis. Addition of DNA gyrase to the mixture dramatically reduces the amount of RNA synthesized. Our data show that the products of the bvg locus, BvgA and BvgS, are directly involved in the regulation of the PTOX promoter in E. coli and that DNA topology may play a role in the induction of transcription.